SAT0139 Analysis of Outcomes After Non-Medical Switching of Anti–Tumor Necrosis Factor Agents. (9th June 2015) - Gibofsky, A.; Skup, M.; Johnson, S.; Chao, J.; Rubin, D.
Abstract : Background: When multiple treatment options within a class are available, substitution with a less expensive or patient-preferred medicine may occur for cost-containment. 1 Objectives: We examined medical outcomes and outpatient resource use associated with cost-based non-medical switching (NMS) of anti-TNF agents. Methods: Electronic health record data (Humedica 2007–2013) were searched to identify patients (≥18 years old) treated with an anti-TNF agent for an immune disorder (rheumatoid arthritis [RA], psoriasis, psoriatic arthritis, ankylosing spondylitis, Crohn's disease [CD], or ulcerative colitis [UC]). A natural language processing algorithm 2 was used to categorize the reason for anti-TNF treatment adjustment (eg, switch, discontinuation) as related to cost or insurance, side effects, or lack of efficacy as indicated in physician chart notes. The NMS sample (N=158) included patients with stable disease in the 90-day baseline period (ie, no anti-TNF treatment change for side effects or lack of efficacy, no emergency room visit, and no hospitalization) who had a cost- or insurance-related switch to a different anti-TNF therapy. The NMS group was matched on key characteristics (including disease type, initial anti-TNF therapy, sex, and age) to controls who were stable and did not experience a medication change due to cost at baseline (N=4, 804). Outpatient resource utilization and rates of anti-TNF treatment adjustment for side effects and lack of efficacy were compared between the NMS group and controls in the 30 days, 90 days, and 1 year after the NMS date in unadjusted and adjusted analyses. Results: Most patients had RA (65% for NMS and 76% for controls); 6% of the NMS group and 3% of controls had UC or CD. Experiencing a cost-based NMS was predictive of an increased likelihood of a subsequent anti-TNF treatment adjustment due to lack of efficacy or side effects during 1 year of follow-up (62% for NMS and 20% for controls, P <0.001) (Figure ). The 1-year medical care utilization also was greater in the NMS group; the mean number of office/clinic visits was 13.0 for the NMS group and 5.8 for controls without NMS ( P <0.001). Analysis of 30- and 90-day outcomes yielded similar results. Conclusions: Non-medical switching of anti-TNF agents was associated with an increase in side effects and lack of efficacy that led to subsequent treatment change as well as increased health care utilization. Cost-related switching of medications in otherwise stable patients may have unintended consequences and should be avoided. References: Morgan S, et al. Open Med. 2009;3:e131–9. Bates M. Proc Nat Acad Sci USA. 1995;92:9977–82. Acknowledgements: Design, study conduct, and financial support for the study were provided by AbbVie Inc. AbbVie participated in the interpretation of data, review, and approval of the abstract; all authors contributed to the development of the publication and maintained control over the final content. Medical writing support was provided by Cathryn M. Carter and Tonya Goodman, of Arbor Communications, Inc; this support was funded by AbbVie. Disclosure of Interest: A. Gibofsky Shareholder of: AbbVie, Amgen, BMS, GSK, Horizon, J&J, Pfizer, Consultant for: AbbVie, Amgen, Celgene, Genentech, Horizon, Iroko, Pfizer, UBC, Speakers bureau: AbbVie, Amgen, Celgene, Genentech, Iroko, Pfizer, UBC, M. Skup Shareholder of: AbbVie, Employee of: AbbVie, S. Johnson Employee of: Medicus Economics, which received payment from AbbVie to participate in this research, J. Chao Shareholder of: AbbVie, Employee of: AbbVie, D. Rubin Grant/research support from: AbbVie, Elan, Prometheus, Shire, Warner Chilcott, Consultant for: AbbVie, Emmi, Genentech, Ironwood, Janssen, Prometheus, UCB, Santarus/Salix, Takeda, Telsar, Vertex